ChatGPT outperforms humans in emotional awareness evaluations - Elyoseph, Zohar; Hadar-Shoval, Dorit; Asraf, Kfir; Lvovsky, Maya (Frontiers in Psychology, 2023)
The artificial intelligence chatbot, ChatGPT, has gained widespread attention for its ability to perform natural language processing tasks and has the fastest-growing user base in history. Although ChatGPT has successfully generated theoretical information in multiple fields, its ability to identify and describe emotions is still unknown. Emotional-Awareness (EA), the ability to conceptualize own and others' emotions, is considered a transdiagnostic mechanism for psychopathology. This study utilized the Level of Emotional Awareness Scale (LEAS) as an objective, performance-based test to analyze ChatGPT’s responses to twenty scenarios and compared its EA performance with that of the general population norms, as reported by Nandrino et al. (2013). A second examination was performed one month later to measure EA improvement over time. Finally, two independent licensed psychologists evaluated the fit-to-context of ChatGPT's EA responses. In the first examination, ChatGPT demonstrated significantly higher performance than the general population on all the LEAS scales (Zscore=2.84). In the second examination, ChatGPT's performance significantly improved, almost reaching the maximum possible LEAS score (Zscore=4.26) Its accuracy levels were also extremely high (9.7/10). The study demonstrated that ChatGPT can generate appropriate EA responses, and its performance improved significantly over time. The study has theoretical and clinical implications, as ChatGPT can be used as part of cognitive training for clinical populations with EA impairments. In addition, ChatGPT’s EA-like abilities may facilitate psychiatric diagnosis and assessment and be used to enhance emotional language. Further research is warranted to better understand the potential risks of ChatGPT and refine it to promote mental health.